2007
DOI: 10.1002/bjs.5996
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of adjuvant uracil–tegafur versus surgery alone for serosa-negative, locally advanced gastric cancer

Abstract: NCT00152243 (http://www.clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
95
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 36 publications
1
95
0
3
Order By: Relevance
“…However, evidence obtained in these trials cannot be applied to Japanese patients, because the standards of surgery performed and actual outcomes of the study populations in these trials were vastly different from those in a similar population in Japan. Apart from the ACTS-GC trial of S-1, the only randomized trial that has shown a survival benefit of adjuvant chemotherapy over surgery in Japan is the NSAS-GC, in which high-dose uracil-tegafur (UFT) was administered for 16 months [24]. Because the subjects in this trial were limited to those with T2/N1-2 disease and the number of cases was small (n = 190) due to slow accrual, the treatment could not be considered as a standard to be widely applied for gastric cancer patients.…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%
“…However, evidence obtained in these trials cannot be applied to Japanese patients, because the standards of surgery performed and actual outcomes of the study populations in these trials were vastly different from those in a similar population in Japan. Apart from the ACTS-GC trial of S-1, the only randomized trial that has shown a survival benefit of adjuvant chemotherapy over surgery in Japan is the NSAS-GC, in which high-dose uracil-tegafur (UFT) was administered for 16 months [24]. Because the subjects in this trial were limited to those with T2/N1-2 disease and the number of cases was small (n = 190) due to slow accrual, the treatment could not be considered as a standard to be widely applied for gastric cancer patients.…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%
“…The literature search identified 11 trial reports, representing 12 RCTs that compared postoperative chemotherapy with surgery alone [12][13][14][15][16][17][18][19][20][21][22]. All of these studies, except for one very recently published trial [22], were part of the meta-analyses described above and will not be discussed further.…”
Section: Postoperative Chemotherapymentioning
confidence: 99%
“…In Japan, clinical studies of chemotherapeutic regimens including oral 5-FU derivatives date back many years, and as a consequence, unique regimens of postoperative chemotherapy have been developed in Japan. In particular, long-term, daily oral treatment with tegafur plus uracil (UFT) as postoperative adjuvant chemotherapy was recently shown to prolong survival in patients with gastric [4], colorectal [5], and lung [6] cancer. To assess the usefulness of postoperative chemotherapy with UFT in breast cancer, the Adjuvant Chemoendocrine Therapy for Breast Cancer (ACETBC) study, the first large clinical trial of its type to be conducted in Japan, was performed [7,8].…”
Section: Introductionmentioning
confidence: 99%